Error leakage and wasted time: sensitivity and effort analysis of a requirements consistency checking process. Issue 12 (20th October 2016) - Li, Wenbin; Hayes, Jane Huffman; Antoniol, Giulio; Guéhéneuc, Yann‐Gaël; Adams, Bram
Abstract: Several techniques are used by requirements engineering practitioners to address difficult problems such as specifying precise requirements while using inherently ambiguous natural language text and ensuring the consistency of requirements. Often, these problems are addressed by building processes/tools that combine multiple techniques where the output from 1 technique becomes the input to the next. While powerful, these techniques are not without problems. Inherent errors in each technique may leak into the subsequent step of the process. We model and study 1 such process, for checking the consistency of temporal requirements, and assess error leakage and wasted time. We perform an analysis of the input factors of our model to determine the effect that sources of uncertainty may have on the final accuracy of the consistency checking process. Convinced that error leakage exists and negatively impacts the results of the overall consistency checking process, we perform a second simulation to assess its impact on the analysts' efforts to check requirements consistency. We show that analyst's effort varies depending on the precision and recall of the subprocesses and that the number and capability of analysts affect their effort. We share insights gained and discuss applicability to other processes built of piped techniques. Abstract : We model and study a process for checking the consistency of temporal requirements and assess error leakage and wasted time. We analyze the input factors of our model to determine the effect that sources of uncertainty may have on the final accuracy of the process. We perform a second simulation to assess error leakage impact on the analysts' efforts to check requirements consistency. We show that analyst's effort varies depending on the precision and recall of the subprocesses and that the number and capability of analysts affect their effort.